Teaching Analogical Reasoning With Co-speech Gesture Shows Children Where to Look, but Only Boosts Learning for Some - Guarino, Katharine F.; Wakefield, Elizabeth M. (Frontiers in Psychology, 2020)
In general, we know that gesture accompanying spoken instruction can help children learn. The present study was conducted to better understand how gesture can support children’s comprehension of spoken instruction and whether the benefit of teaching though speech and gesture over spoken instruction alone depends on differences in cognitive profile – prior knowledge children have that is related to a to-be-learned concept. To answer this question, we explored the impact of gesture instruction on children’s analogical reasoning ability. Children between the ages of 4 and 11 years solved scene analogy problems before or after speech alone or speech and gesture instruction while their visual attention was monitored. Our behavioral results suggest a marginal benefit of gesture instruction over speech alone, but only 5-year-old children showed a distinct advantage from speech+gesture instruction when solving the post-instruction trial, suggesting that at this age, children have the cognitive profile in place to utilize the added support of gesture. Furthermore, while speech+gesture instruction facilitated effective visual attention during instruction, directing attention away from featural matches, and towards relational information, was pivotal for younger children’s success post instruction. We consider how these results contribute to the gesture-for-learning literature and consider how the nuanced impact of gesture is informative for educators teaching tasks of analogy in the classroom.